The determinants of military expenditure in Rwanda - Dlamini, Nakiwe (School of Economics, 2025)
Military expenditure is a critical component of every nation's central government budget. Despite its important role, very few studies attempt to investigate the determinants of military expenditure for individual countries in the third world. Most studies have focused on cross country and panel studies largely for developed economies. This study addresses these issues by investigating the determinants of military expenditure in Rwanda, a country that has experienced conflict and civil unrest. No studies for Rwanda had been published, regardless of the growing military expenditure. A range of factors such as economic, political, or strategic conditions can drive the demand for defence expenditure. This paper employs a general model of demand for military expenditure and estimates it using the Autoregressive Distributed Lag (ARDL) approach, over the period 1973 to 2022. The results provide strong evidence that trade openness, foreign direct investment (FDI), democracy, genocide and real GDP per capita play a crucial role in determining military expenditure in Rwanda. According to the conclusions drawn from the study, government initiatives should prioritize trade openness to result in less government spending on the defence sector, which in turn frees up funds for other government projects. Additionally, efforts to attract FDI should be intensified, as FDI inflows can lower the intensity of global conflict, promote cooperation and result to a reduced level of military spending.